2021
DOI: 10.1021/acsomega.1c04809
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Viscosity and Thermal Characteristics of Polyolefins/Solvent Mixtures: Applications for Plastic Pyrolysis

Abstract: Plastic pollution is one of the biggest environmental problems that the world is currently facing. Pyrolysis is a frontier technique aimed at converting plastic waste back into virgin-quality resin. However, the transfer of the waste plastic feed into the pyrolysis reactor must be optimized before the process can be upscaled to a continuous process. In this study, a new solvent that reduces the viscosity of molten plastic was introduced and characterized. The results revealed that the polymers are soluble in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
2
11
1
Order By: Relevance
“…In a prior article, we demonstrated that paraffin wax is an effective solvent for dissolving waste plastics and reducing the mixture viscosity by temperature adjustment . In the results presented here, we compare paraffin wax and pyrolysis wax to each other.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…In a prior article, we demonstrated that paraffin wax is an effective solvent for dissolving waste plastics and reducing the mixture viscosity by temperature adjustment . In the results presented here, we compare paraffin wax and pyrolysis wax to each other.…”
Section: Resultsmentioning
confidence: 90%
“…In our previous study and pyrolysis pilot plant experiments, we demonstrated that the complete dissolution of polyolefin plastics in paraffin wax at a 1:1 (wt) ratio mixture is possible at temperatures over 200 °C, and their viscosities are suitable for flowing the mixture into a pyrolysis reactor. In addition, those prior experiments also demonstrated that both the plastics and the paraffin wax in the mixture were degraded into pyrolysis products (paraffins were converted to alkenes) .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations